2020
DOI: 10.7717/peerj.8732
|View full text |Cite
|
Sign up to set email alerts
|

Rare ground data confirm significant warming and drying in western equatorial Africa

Abstract: Background The humid tropical forests of Central Africa influence weather worldwide and play a major role in the global carbon cycle. However, they are also an ecological anomaly, with evergreen forests dominating the western equatorial region despite less than 2,000 mm total annual rainfall. Meteorological data for Central Africa are notoriously sparse and incomplete and there are substantial issues with satellite-derived data because of persistent cloudiness and inability to ground-truth estimates. Long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
4
20
0
Order By: Relevance
“…The results in Table 1 agree well with those of Nicholson et al (2019), which found CHIRPS2 and PERSIANN-CDR to be more accurate than TRMM and GPCC in the Congo Basin after 1998. Prior work has also demonstrated that CHIRPS2 is among the best P products available for central Africa and outperforms TRMM and PERSIANN-CDR on a monthly basis (Dembélé and Zwart, 2016;Camberlin et al, 2019;Nicholson et al, 2019), consistent with the results in Table 1. Given the decreasing availability of Congolese rain gauge data in the GPCC database and the difficulty of measuring P with satellite remote sensing in central Africa (McCollum et al, 2000;Yin and Gruber, 2010;Awange et al, 2016;Nicholson et al, 2018), it is not surprising that the GPCC-based products generally displayed higher errors.…”
Section: Triple Collocation Of Precipitation Datasetssupporting
confidence: 84%
See 4 more Smart Citations
“…The results in Table 1 agree well with those of Nicholson et al (2019), which found CHIRPS2 and PERSIANN-CDR to be more accurate than TRMM and GPCC in the Congo Basin after 1998. Prior work has also demonstrated that CHIRPS2 is among the best P products available for central Africa and outperforms TRMM and PERSIANN-CDR on a monthly basis (Dembélé and Zwart, 2016;Camberlin et al, 2019;Nicholson et al, 2019), consistent with the results in Table 1. Given the decreasing availability of Congolese rain gauge data in the GPCC database and the difficulty of measuring P with satellite remote sensing in central Africa (McCollum et al, 2000;Yin and Gruber, 2010;Awange et al, 2016;Nicholson et al, 2018), it is not surprising that the GPCC-based products generally displayed higher errors.…”
Section: Triple Collocation Of Precipitation Datasetssupporting
confidence: 84%
“…While PER-SIANN is also available without the GPCC gauge corrections that make PERSIANN-CDR so similar to GPCC v7 and TRMM 3B43 over the Congo Basin (Nguyen et al, 2018), it was not used here because it severely overestimates P across Africa (Beighley et al, 2011;Thiemig et al, 2012). Several recent studies have found that TRMM Version 7 3B43 and PERSIANN-CDR both perform reasonably well over central 4192 M. W. Burnett et al: Data-driven estimates of evapotranspiration and its controls in the Congo Basin Africa (Munzimi et al, 2015;Awange et al, 2016;Camberlin et al, 2019).…”
Section: Water Balance Data Sourcesmentioning
confidence: 99%
See 3 more Smart Citations